Exploring the Societal Attitudes: A Sentiment Analysis of the Public Views on the LGBT Community Using Natural Language Processing - Pasion, Charis; Daniel, Kevin Jay; Huelgas, Joseph M. A; Morancil, Angelo; De Paula, Eddie; Bunda, Niel (Eximia, 2025)
This study investigates global attitudes toward the LGBTQ community through sentiment and thematic analysis of Twitter data. Utilizing the OSEMN framework, the research analyzes a dataset of 29,890 tweets collected over a six-day period. After data preprocessing using natural language processing techniques, exploratory analysis revealed key linguistic patterns and commonly discussed topics. Latent Dirichlet Allocation (LDA) topic modeling uncovered four dominant themes within the discourse: (1) promoting sexual health through political engagement, (2) balancing freedom of expression and inclusivity in digital spaces, (3) empowerment and transformation through representation, and (4) addressing prejudice and discrimination in political leadership. Sentiment analysis results show that 47.73% of the tweets expressed positive sentiment, often reflecting support, celebration, and advocacy for LGBTQ rights and identity. In contrast, 26.25% were negative, with many tweets containing hate speech, misinformation, or stigmatizing language tied to religious or political ideologies. The remaining 26.02% were classified as neutral, reflecting a mix of informational or non-committal content. Visualizations such as word clouds, bi-grams, tri-grams, and a network graph, supported the interpretation of topic clusters and revealed the nuanced dynamics of online LGBTQ discourse. The findings suggest that Twitter functions both as a platform for visibility and affirmation, and as a space where prejudice persists. This disparity emphasizes the ongoing need of awareness and advocacy in online spaces and the intricacy of digital environments in influencing public perceptions of marginalized groups.